IMPLEMENTASI CHATGPT SEBAGAI ALAT BANTU PENGEMBANGAN PROFESIONALISME GURU DI SMA NEGERI 13 MALUKU BARAT DAYA - Patty, Jusak; Lekatompessy, Jeny; Lekatompessy, Felicia Miranda (Universitas Mataram, 2025)
The development of artificial intelligence (AI) technology, particularly ChatGPT, has opened new opportunities in education, yet many teachers still struggle to integrate it into their teaching practices, especially in remote areas like SMA Negeri 13 Tiakur, Southwest Maluku. Limited digital infrastructure and minimal exposure to recent educational innovations hinder teachers' digital competency development. This community service aimed to enhance teachers' competency in using ChatGPT as a teaching tool through a comprehensive workshop. The activity was conducted on November 17, 2023, using an experiential learning approach with presentation, demonstration, hands-on practice, and reflective discussion methods involving 15 teachers as participants. Evaluation results showed high satisfaction levels (average 3.41 out of 4.0), with 40% of teachers focusing on using ChatGPT for lesson plan development, 33.3% for assessment creation, and 26.7% for teaching material development. The workshop successfully improved teachers' understanding and skills in integrating ChatGPT into their teaching practices, marked by the establishment of a community of practice for program sustainability.